KEABSAHAN AKTA NOTARIS DISAAT TERJADI KETIDAKSESUAIAN JABATAN SEBAGAI PEJABAT PEMBUAT AKTA TANAH (PPAT) DENGAN WILAYAH YANG BERBEDA - DAUD WIDYA PRANATA SEPTIADI (PREMISE LAW JURNAL, 2017)
Regulated in Article 17, letter g of UUJN which states that a Notary is prohibited to do tow positions as a PPAT outside of a notarial area. In other words, a Notary can also function as a PPAT when it is in the same notarial area. Article 19 of UUJN states that a Notary has to take his position in only one area in a town or a district, and he has the authority in the whole provincial territory of his position. A Notary has to have only one office; it means that he is prohibited to have branch office, subsidiary and/or the other types of office, and all deeds have to made in his office except drawing up certain deeds.Keywords: Two Positions, Notary, PPAT, Different Area